(untitled) (The Review of Diabetic Studies, 2024)
The mode of care provided through the efforts of interdisciplinary teams is a cornerstone approach in the improvement of patient results in a wide range of healthcare environments. An integrative analysis of the impact of inter professional cooperation between nursing , medicine, dentistry , health administration , social work , and pharmacy practitioners in the management of chronic diseases and the provision of patient care is discussed. The integration of multiple healthcare fields creates a synergistic effect, which improves patient results, patient satisfaction, and efficiency in the use of resources. Studies have revealed that a team-based approach in the management of patient care results in a substantial improvement in the management of disease indicators, a reduction in hospitalization rates, and increased patient participation. This paper aims to integrate existing knowledge on collaborative care approaches, challenges associated with the implementation of such approaches, and measurable outcomes in a wide range of medical disciplines.